Reforma e innovación educativa. Consideraciones teóricas para la investigación crítica - Miranda Camacho, Guillermo (2007)
In this essay we propose to do a critical approach to the education reform and innovation. Our interest is to examine the nature, ideological-political fundament and comparative characteristics between two manifestations of the educational change. To accomplish this task we initiate our exposition with an analysis of the principal sociohistoric framework of the beginning of the education changes and innovations: the technological boom of the eighties decade. In second place, we explore some fundamental characteristics, in comparative perspective, of education changes and innovations. In a third moment, we expos, in succinct way, some elements that we considerate basics to a hermeneutical and critical approach, to the models in theory of the educational changes. In the forth section, we move deeper in to the knowledge of the historical- structural dimension of the educational changes, as process witch take place in the changes of the social system. In the fifth and last part we do a theory excursus about the educational functions as sociostructural references to the education changes and innovations. This work is part of a process, that we systematize in other essays, with the intentions of contribute with elements to a critical hermeneutical vision of the process of educational changes. This is a product of the professorship “education, development and democracy: Uladislao Gámez Solano” of The Investigation and Teaching Education Center of the National University in Costa Rica.